2016
DOI: 10.1038/srep39465
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Ultrasensitive Photo-detection Through Control of Interface Properties in Molybdenum Disulfide Atomic Layers

Abstract: The interfaces in devices made of two-dimensional materials such as MoS2 can effectively control their optoelectronic performance. However, the extent and nature of these deterministic interactions are not fully understood. Here, we investigate the role of substrate interfaces on the photodetector properties of MoS2 devices by studying its photocurrent properties on both SiO2 and self-assembled monolayer-modified substrates. Results indicate that while the photoresponsivity of the devices can be enhanced throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Lu et al [31] observed significant N-doping in thin MoS 2 films on SiO 2 , which is dominated by charge traps at the sample−substrate interface by scanning tunneling microscopy. The charge trapping at the SiO 2 −MoS 2 interface and its effects on the characteristics of the MoS 2 field effect transistors and photodetection devices have been studied [32][33][34]. Very recently, Kim et al [35] investigated the triboelectric charges of a graphene/SiO 2 system, and found that the triboelectric charges are trapped at the air-SiO 2 interface underneath the graphene and act as ghost floating gates.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [31] observed significant N-doping in thin MoS 2 films on SiO 2 , which is dominated by charge traps at the sample−substrate interface by scanning tunneling microscopy. The charge trapping at the SiO 2 −MoS 2 interface and its effects on the characteristics of the MoS 2 field effect transistors and photodetection devices have been studied [32][33][34]. Very recently, Kim et al [35] investigated the triboelectric charges of a graphene/SiO 2 system, and found that the triboelectric charges are trapped at the air-SiO 2 interface underneath the graphene and act as ghost floating gates.…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [178] observed significant N-doping in thin MoS 2 films on SiO 2 , dominated by charge traps at the sample − substrate interface by STM. Further, the charge trapping and its effects on the characteristics of the MoS 2 field-effect transistors and photodetection devices were investigated [179,180]. Liu et al [181] claimed to generate anomalously high DC using a sliding Schottky nano-contact in a sliding semiconductor-metal contact (on MoS 2 multilayers/Ag).…”
Section: Interfacial Charge Transfermentioning
confidence: 99%